Child and adolescent mental health services during the COVID-19 epidemic in Slovenia: Comparison with other European countries : Delovanje služb za duševno zdravje otrok in mladostnikov v času epidemije COVID-19 v Sloveniji: primerjava z drugimi evropskimi državami - Gregorič Kumperščak, Hojka; Podlesnik Peršak, Ivan (Acta Medico-Biotechnica, 2023)
Purpose: To evaluate the impact of the COVID-19 epidemic on child and adolescent mental health services (CHAMS) during the first and second epidemic wave.Methods: Members of the Slovenian Association for Child and Adolescent Psychiatry (n=66) were invited to participate in the study. The survey involved two semi-structured questionnaires on CHAMS and clinical and organizational issues with respect to the first and second COVID-19 waves. The findings were compared with similar studies conducted in other European countries.Results: Eighteen members fulfilled the first and seven the second questioner. Thirty-three percent of respondents reported that their CHAMS colleagues were assigned to the COVID-19 wards during the first and 43% in the second wave. The CHAMS were more affected by the public health measures for COVID-19 during the first wave. During the first wave, half of the respondents experienced worsening anxiety disorders, while an increase in all mental disorders was reported during the second wave.Conclusion: A concerning finding of this study was limited access to CHAMS as a result of public health measures, especially during the first wave. But the provision of services in Slovenia was not as severely limited as elsewhere in Europe. CHAMS in Slovenia were able to provide better employee safety measures in terms of COVID-19 infections compared to other European countries. CHAMS employees in Slovenia were more frequently transferred to COVID-19 wards compared to their European colleagues, despite the fact that they were faced with increasing numbers of children and adolescents with mental disorders.
Keywords: adolescents, COVID-19, children, mental disorders, mental health, psychiatry